PELATIHAN PEMBUATAN SABUN CAIR RAMAH LINGKUNGAN CUCI PIRING DAN BAJU UNTUK MENINGKATKAN KETERAMPILAN IBU- IBU PKK DI KELURAHAN BOJONGSALAMAN KOTA SEMARANG - Kusmiyati Kusmiyati; Dony Satriyo Nugroho; Khoirunisa Riska Pradana; Vivi Normasari; Karina Ayu Mutia (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Introduction. The utilize of soaps that are not environmentally friendly is still common among the open. The need of information approximately environmentally friendly soap fixings is one of the contributing components. Purpose. This benefit points to extend information and abilities related to making environmentally friendly fluid soap, as well as a new commerce advancement for Family Welfare Strengthening (PKK) in Bojongsalaman Town RT 3 / RW 4 Semarang City. Method. The method of this Community service action is training. This community benefit action was carried out with the nearness of 20 PKK womens, 2 speakers and the action organizing committee. The activity starts with the introduction of fundamental beginning from the definition of soap, the working standards of soap, apparatuses and materials and the steps of making it. The activity proceeded with the hone of making environmentally friendly fluid soap with the heading of the speaker. Results. Pretest comes about of preparing as much as 10% get it almost environmentally friendly soap. Whereas the comes about of the preparing posttest were 90% caught on approximately environmentally friendly soap. An increment of 78% in trainees' information of environmentally friendly fluid soap appears the victory of this benefit. Conclusions and recomendation. This training expanded the information and aptitudes of PKK womne in making environmentally friendly fluid dish soap. It is hoped that the participants of this service can channel the information to the surrounding community.